2011
DOI: 10.1371/journal.pone.0028521
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Studies of a Bothropic Myotoxin Complexed to Rosmarinic Acid: New Insights into Lys49-PLA2 Inhibition

Abstract: Snakebite envenoming is an important public health problem in many tropical and subtropical countries, and is considered a neglected tropical disease by the World Health Organization. Most severe cases are inflicted by species of the families Elapidae and Viperidae, and lead to a number of systemic and local effects in the victim. One of the main problems regarding viperidic accidents is prominent local tissue damage whose pathogenesis is complex and involves the combined actions of a variety of venom componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 89 publications
5
39
0
1
Order By: Relevance
“…This compound demonstrates antimyotoxic properties and inhibits edema induced by crude B. jararacussu snake venom and its basic PLA 2 s [36, 55]. The three-dimensional structure of the PrTX-I, rosmarinic acid complex, was elucidated by Santos and collaborators [68], where rosmarinic acid was observed located at the entrance of the hydrophobic channel monomer A of the PrTX-I dimer via an interaction between hydrogen bonds and hydrophobic contacts in the same monomer. Interactions were also observed between rosmarinic acid and a residue of the C-terminal region of the monomer B.…”
Section: Structural Characterization Of Pla2 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound demonstrates antimyotoxic properties and inhibits edema induced by crude B. jararacussu snake venom and its basic PLA 2 s [36, 55]. The three-dimensional structure of the PrTX-I, rosmarinic acid complex, was elucidated by Santos and collaborators [68], where rosmarinic acid was observed located at the entrance of the hydrophobic channel monomer A of the PrTX-I dimer via an interaction between hydrogen bonds and hydrophobic contacts in the same monomer. Interactions were also observed between rosmarinic acid and a residue of the C-terminal region of the monomer B.…”
Section: Structural Characterization Of Pla2 Inhibitorsmentioning
confidence: 99%
“…Interactions were also observed between rosmarinic acid and a residue of the C-terminal region of the monomer B. The interaction between the rosmarinic acid molecule with the hydrophobic channel (monomer A) and the C-terminal region (myotoxic site, monomer B) suggests two mechanisms of myotoxicity inhibition [68]. …”
Section: Structural Characterization Of Pla2 Inhibitorsmentioning
confidence: 99%
“…Molecular comparisons of the structures were performed using the Coot v.0.7 program (Emsley and Cowtan, 2004) with only C a coordinates. The structures of MjTX-II/ stearic acid (PDB ID 1XXS) (Watanabe et al, 2005), BaspTX-II (PDB ID 1CLP) in its native form (Arni et al, 1995) and complexed to suramin (PDB ID 1Y4L) (Murakami et al, 2005), BthTX-I (PDB ID 3HZD), BthTX-I/PEG4000 (PDB ID 3IQ3), BthTX-I/BPB (PDB ID 3HZW), PrTX-I/BPB (PDB ID 2OK9) (Fernandes et al, 2010), BthTX-I/atocopherol (PDB ID 3CXI), PrTX-I (PDB ID 2Q2J), PrTX-I/atocopherol (PDB ID 3CYL) (dos Santos et al, 2009), PrTX-I/Rosmarinic acid (PDB ID 3QNL) (dos Santos et al, 2011a), PrTX-II/fatty acid (PDB ID 1QLL) (Lee et al, 2001), BnSP-6 and BnSP-7 (PDB ID 1PC9 and 1PA0 respectively) (Magro et al, 2003) and BnIV/ Myristic acid (PDB ID 3MLM) (Delatorre et al, 2011) were used in the comparative analysis.…”
Section: Comparative Analysismentioning
confidence: 99%
“…The polyphenol rosmarinic acid isolated from diverse species of the Boraginaceae and Lamiaceae, reduced 80% and 90 % the muscle damage and the neuromuscular blockade induced by PrTX-I (a PLA 2 Lys 49 from the venom of Bothrops pirajai) on mice neuromuscular (phrenic-diaphragm) preparations. X-ray crystallographic studies between two molecules demonstrated that rosmarinic acid obstruct the entrance of the hydrophobic channel in PrTX-I affecting the interaction with membrane [37].…”
Section: Discussionmentioning
confidence: 99%